The law of fraud and the forensic investigator - Debenham, David (Toronto : Carswell, 2012)
'This book gives lawyers, accountants, internal auditors, and other investigators both an in-depth analysis of fraud, as well as the latest tools, techniques, and methods of handling internal or external fraud engagement. It will provide guidance in terms of documenting fraud, preparing evidence, conducting a fraud investigation, and acting as an expert consultant or expert witness in any eventual litigation or proceedings. It represents the latest thinking on each area of the process, written by a commercial litigation lawyer, trained as both a management accountant and forensic investigator, who has been involved in several prominent cases as the head of the fraud recovery team.'--pub. desc.
Includes bibliographical references and index.
Keywords: Fraud -- Canada; Fraud investigation -- Canada